Kepemimpinan Kepala Sekolah Dalam Mewujudkan Kultur Sekolah Di SD Negeri 1 Papahan Tasikmadu Karanganyar Tahun 2015/2016 - Yudha Pertiwi, Denisa; , Minsih S. Ag, M. Pd (2016)
ABSTRACT Denisa Yudha Pertiwi/A510120187. MAKING THE PRINCIPAL LEADERSHIP CULTURE SCHOOL IN SD NEGERI 1 PAPAHAN TASIKMADU KARANGANYAR YEAR 2015/2016. Essay. The Faculty of Education, University of Muhammadiyah Surakarta. March, 2016. The purpose of this study was to describe: 1) the characteristics of school leadership in SD Negeri 1 Papahan Tasikmadu Karanganyar, 2) the strategy of school leadership in realizing the school culture in SD Negeri 1 Papahan Tasikmadu Karanganyar and 3) the characteristics of school culture built by principal SD Negeri 1 Karanganyar Papahan Tasikmadu. Type of research is descriptive qualitative research, while the design of studies using phenomenology. For the technique of data collection is done through observation, interviews and documentation, with informants consisted of principals, teachers and students of SD Negeri 1 Papahan Tasikmadu Karanganyar. The validity of the data using triangulation of data sources and triangulation techniques. Data were analyzed through data reduction steps, the data display / presentation of the data and conclusions / verification. The results showed that 1) the principal of SD Negeri 1 Papahan Tasikmadu Karanganyar are quite good in leadership 2) the principal has been successful in carrying out its duties and powers in accordance with the kind of leadership that is implemented, which is included in the democratic leadership and leadership Participatory 3) strategy principals consist of a wide variety of activities and special programs so that school culture is well established in accordance with the objectives of the school 4) the school culture in SD Negeri 1 Papahan Tasikmadu Karanganyar very diverse, in its implementation required awareness and habituation every day both in the classroom and outside class. Keywords: leadership, principals, school culture.